If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 15 + -1(-4) Multiply -1 * -4 y = 15 + 4 Combine like terms: 15 + 4 = 19 y = 19 Solving y = 19 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 19
| x^2-3x-8=-4x+4 | | -6(n-2)-1=-(4+7n) | | -11n^2=9-2n | | 54m= | | 14g-5g-5g-3G=17 | | -3-3r=-6(5+5r) | | x^2-13x+39=3 | | x^2=3x-28 | | 3x-5=7x-45 | | -33-2b=-5+8(1-b) | | 2w-w+4w+w-5w=8 | | 5x+4=2y | | 6(4m-6)=30+2m | | sin(3x)-sin(7x)=0 | | -2x+17=-6(x+1)-5 | | 3m-2m-m+m=7 | | (1-3x)(9x-7)=0 | | -10x+8y=10 | | (x+1)2=144 | | 16+4r=7r+7 | | 15s-6s-6s=18 | | -8+5a=-93 | | 9x^2+4=-77 | | 5x+6y=226.19 | | 4x^2-25x+27=-4x+7 | | 27+x=68 | | 4s-3s=4 | | 2-10i+5x=17-5yi | | 6k-3=-93 | | y+4=4(x-3) | | 8n+n=8 | | (2x+5y)(x^2+4xy-5y^2)= |